Adipokinetic Hormones Enhance the Efficacy of the Entomopathogenic Fungus Isaria fumosorosea in Model and Pest Insects - Gautam, Umesh Kumar; Hlávková, Daniela; Shaik, Haq Abdul; Karaca, Ismail; Karaca, Gürsel; Sezen, Kazim; Kodrík, Dalibor (Pathogens (Basel, Switzerland), 2020)
Insect adipokinetic hormones (AKHs) are neuropeptides with a wide range of actions, including the control of insect energy metabolism. These hormones are also known to be involved in the insect defence system against toxins and pathogens. In this study, our aim was to demonstrate whether the application of external AKHs significantly enhances the efficacy of the entomopathogenic fungus Isaria fumosorosea in a model species (firebug Pyrrhocoris apterus) and pest species (Egyptian cotton leafworm Spodoptera littoralis and pea aphid Acyrthosiphon pisum). It was found that the co-application of Isaria with AKHs significantly enhanced insect mortality in comparison to the application of Isaria alone. The mode of action probably involves an increase in metabolism that is caused by AKHs (evidenced by the production of carbon dioxide), which accelerates the turnover of Isaria toxins produced into the infected insects. However, several species-specific differences probably exist. Intoxication by Isaria elicited the stimulation of Akh gene expression and synthesis of AKHs. Therefore, all interactions between Isaria and AKH actions as well as their impact on insect physiology from a theoretical and practical point of view need to be discussed further.
Keywords: entomopathogen; insect pest; carbon dioxide production; AKH; mortality; metabolism